Cultures of Yusin : South Korea in the 1970s - Ryu, Youngju, 1974- (Perspectives on contemporary Korea., 2018)
"Cultures of Yusin examines the turbulent and yet deeply formative years of Park Chung Hee's rule in South Korea, focusing on the so-called Yusin era (1972-79). Beginning with the constitutional change that granted dictatorial powers to the president and ending with his assassination, Yusin was a period of extreme political repression coupled with widespread mobilization of the citizenry towards the statist gospel of modernization and development. While much has been written about the political and economic contours of this period, the rich complexity of its cultural production remains obscure. This edited volume brings together a wide range of scholars to explore literature, film, television, performance, music, and architecture, as well as practices of urban and financial planning, consumption, and homeownership. Examining the plural forms of culture's relationship to state power, the authors illuminate the decade of the 1970s in South Korea and offer an essential framework for understanding contemporary Korean society"--